Validação e adaptação transcultural do instrumento Modified Advanced Practice Nursing Role Delineation Tool para o português do Brasil - Minosso, Kamila Caroline (2022)
Population aging and increasing changes in the health-disease process require changes in the performance of health professionals. Faced with this scenario, nursing is reconfiguring the performance of its professionals and its functions are expanding, such as Advanced Practice Nursing. The scope of the roles of these professionals in the world is diverse, therefore, making their broad understanding difficult, and studies on the practice in the Brazilian context are incipient. To assess this function, there are instruments available in a foreign language, however, none are in Portuguese. In this way, a valid and reliable tool would help those responsible in the country to identify and define the profile of nurses' activities that could be considered advanced nursing practice.Therefore, the objective of this study emerges to carry out the translation, cultural adaptation, and psychometric validation of the Modified Advanced Practice Nursing Role Delineation Tool into Brazilian Portuguese. A methodological study of instrument validation, quantitative, using the Modified Advanced Practice Nursing Role Delineation Tool, divided into three stages: 1) Process of translation and cultural adaptation; 2) Construct validation; and, 3) Clinical validation of the instrument. The first stage, of evaluation by the committee of judges, took place from July to September 2020, the second stage of pre-test, with a sample of 30 nurses working in a city in western Paraná, the collection was carried out from November 2020 to January 2021 and the third stage, with 207 nurses working in 15 Brazilian states, was from February to September 2021. The stability and reliability of the instrument were verified through the content validity index, Kappa coefficient, while to assess internal consistency, Cronbach's alpha was used, descriptive and inferential statistics were used, and the z test was used to compare proportions.In the evaluation by the committee of judges, the Kappa index obtained a substantive agreement of 0.68 and the intraclass correlation was 0.80, and the version for application in the pre-test was approved. The reliability by Cronbach's Alpha was high (0.98) and substantial intraclass correlation (0.61), in the application of the pre-test, being considered approved for validation with professionals. In the clinical validation stage, the scale obtained an alpha greater than 0.80 in almost all domains, except for the Education domain, referring to Florianópolis, SC (0.786). Regarding the domains performed by nurses, a Cronbach's alpha value of 0.92 was observed for the Direct Comprehensive Care dimension, 0.833 for the Systems Support dimension, 0.827 for Education, 0.860 for Research, and 0.912 for Publication. Through these results, it is possible to affirm that the items are homogeneous and that the scale consistently measures the characteristic for which it was created. Considering the criterion of eigenvalue greater than one, 8 factors were obtained with 79.38% of the variance explanation, different from the original scale, with five factors. This model was called model 2 and was able to closely reproduce the population covariance. The tool was considered culturally and psychometrically adapted and can be used in the country to identify the skills of primary care nurses for the development of advanced nursing practices.